(untitled) (Asian Journal of Current Engineering and Maths, 2013)
Several applications of practical interest stem from the capability to monitor and store packet-level traces in a 3G network. Among them, the possibility to infer and locate network problems (e.g. persistent shortage of capacity, or equipment mis functioning), in the core and radio sections, without direct access to the equipments. This approach yields strong practical benefits, given the costs and complexity of accessing network equipments, especially in the Radio Access Network. At the same time, it exposes practical issues - e.g. the need to dynamically locate the traffic sources (Mobile Stations) - and theoretical problems - e.g. inferring congested cells from Routing-Area level TCP measurements. We report on our work-in-progress aimed at implementing such mechanisms on top of an advanced monitoring system now deployed in an operational network